Comparisons of guardianship laws and surrogate decision-making practices in China, Japan, Thailand and Australia: a review by the Asia Consortium, International Psychogeriatric Association (IPA) capacity taskforce. (9th January 2015) - Tsoh, Joshua; Peisah, Carmelle; Narumoto, Jin; Wongpakaran, Nahathai; Wongpakaran, Tinakon; O'Neill, Nick; Jiang, Tao; Ogano, Shoichi; Mimura, Masaru; Kato, Yuka; Chiu, Helen
ABSTRACT: Background: The International Psychogeriatric Association (IPA) capacity taskforce was established to promote the autonomy, proper access to care, and dignity of persons with decision-making disabilities (DMDs) across nations. The Asia Consortium of the taskforce was established to pursue these goals in the Asia-Pacific region. This paper is part of the Asia Consortium's initiative to promote understanding and advocacy in regard to surrogate decision-making across the region. Method: The current guardianship laws are compared, and jurisdictional variations in the processes for proxy decision-making to support persons with DMDs and other health and social needs in China, Japan, Thailand, and Australia are explored. Results: The different Asia-Pacific countries have various proxy decision-making mechanisms in place for persons with DMDs, which are both formalized according to common law, civil law, and other legislation, and shaped by cultural practices. Various processes for guardianship and mechanisms for medical decision-making and asset management exist across the region. Processes that are still evolving across the region include those that facilitate advanced planning as a result of the paucity of legal structures for enduring powers of attorney (EPA) and guardianship in some regions, and the struggle to achieve consensual positions in regard to end-of-life decision-making. Formal processes for supporting decision-making are yet to be developed. Conclusions: The diverse legal approaches to guardianship and administration must be understood to meet the challenges of the rapidly ageing population in the Asia-Pacific region. Commonalities in the solutions and difficulties faced in encountering these challenges have global significance.